ARTISTIC IMAGE OF THE DIVISION IN THE SERBIAN PEOPLE IN THE 20TH AND 21ST CENTURIES: (PROJECTION OF IDEAS, CAUSES AND CONDITIONS OF DIVISION IN THE PROSE AND POETRY OF RADOMIR STOJANOVIĆ) (Heritage, 2024)
The work on the example of stories from the collection Duša domа (Soul of home) and poetry by Radomir Stojanović, in the light of the Book about Tito by Dobrica Ćosić and the autopoetic comments of Dragomir Kostić "While the book was in print", reveals the projection of the truth about Serbian divisions into us and them in the 20th and 21st centuries and the attitude of Serbs towards history as reality.Also, we list important historical facts that are a necessary condition to understand the suffering fate of the Serbian people in Kosovo and Metohija, as well as conflicts within the Serbian people, which were certainly caused by major historical events. The focus of the analysis is focused on the relationship between us and others within the same nation, that is, the ideological divisions caused by the divisions during and after the Second World War in Serbia. This is a condition to look deeper and understand the nature and essence of the connection and relationship and the division between us and others and/or ours and others, not only between Serbs and Albanians. The very science of literature implies that we always understand art as a type of "cognitive instrument by means of which the truths about the human being are revealed."From an analytical review of the projection of artistic ideas and images of Radomir Stojanović and Dragomir Kostić, in the light of the great thinker of history Dobrica Ćosić and his projections of Titoism, the work brings several magisterial conclusions. They are a contribution to a new reading and interpretation of the artist's work and the relationship to the theme of us and others and the division of us and us within the Serbian people.
Keywords: Radomir Stojanović, Dobrica Ćosić, Dragomir Kostić, we and others, we and we, Serbs, Serbia, Kosovo and Metohija, political party, Goli otok